2019
DOI: 10.25095/mufad.607218
|View full text |Cite
|
Sign up to set email alerts
|

Muhasebe Meslek Mensuplarının Sundukları Hizmet Kalitesinin Müşteri Memnuniyeti Üzerindeki Etkisi: Erzincan Örneği

Abstract: Çalışmanın amacı, muhasebe meslek mensuplarının hizmet kalitesinin müşteri memnuniyeti üzerindeki etkisini ortaya koymaktır. Ayrıca, müşterilerin memnuniyet seviyesinin belirlenmesi de amaçlanmaktadır. Bu çalışmanın kapsamı, Erzincan Ticaret ve Sanayi Odası'na kayıtlı ve bir muhasebeciden hizmet alan şirketlerden oluşmaktadır. Muhasebe meslek mensuplarının sunduğu hizmet kalitesini belirlemek için SERVQUAL ölçeği kullanılmıştır. Ayrıca, müşteri memnuniyetini ölçmek için anket formuna bazı sorular eklenmiştir. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Reliability, empathy and tangibles were found to have a positive effect in terms of dimensions. Kurnaz and Güner (2019) conducted a similar study on accountants in Erzincan province and as a result found that physical characteristics, reliability, assurance and empathy dimensions had a positive effect on customer satisfaction, whereas responsiveness dimension had an adverse effect. The difference of this study from the other two studies in the literature is that this study focuses on a single sector, which is hairdressers and barbers, and is conducted in the province of Istanbul.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Reliability, empathy and tangibles were found to have a positive effect in terms of dimensions. Kurnaz and Güner (2019) conducted a similar study on accountants in Erzincan province and as a result found that physical characteristics, reliability, assurance and empathy dimensions had a positive effect on customer satisfaction, whereas responsiveness dimension had an adverse effect. The difference of this study from the other two studies in the literature is that this study focuses on a single sector, which is hairdressers and barbers, and is conducted in the province of Istanbul.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Many studies in the national literature mention the effect of service quality dimensions on satisfaction. When the studies conducted in this context are examined, it is seen that service quality and dimensions have an effect on satisfaction in thermal hotel businesses (Akşit Aşık, 2016;İlban, Bezirgan and Çolakoğlu, 2016), ready-made clothing industry (Güven, Yılmaz and Güven, 2018;Öztürk, 2019), health services (Beydoğan and Kalyoncuoğlu 2017;Semiz, Semiz and Güneş, 2023), public services (Demirbağ and Yozgat, 2016;Doğan, 2020), accommodation services (Doğan, 2023;Kazan and Güneş, 2022;Nalbant and Demiral, 2019;Onurlubaş and Öztürk, 2020), airline transportation (Gürler and Erturgut, 2019;Yangınlar and Tuna, 2020), banking services (Işık, Akbolat and Ünğan, 2013;Karadeniz andGözüyukarı, 2016: Tan, İğde, Çelik andBuğan, 2016), food and beverage sector (Kocagöz and Eyitmiş, 2020), financial services (Kurnaz and Güner, 2019;Tosunoğlu, Cengiz and Dönmez, 2019), logistics services (Yıldız, Çiğdem and Aslan, 2018;Onurlubaş and Gümüş, 2020), retail sector (Yücekaya, Rençber and Sönmez, 2015) and maritime transportation (Yüksel and Önaçan, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%